2016
DOI: 10.1053/j.semperi.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

What we have learned about the role of 17-alpha-hydroxyprogesterone caproate in the prevention of preterm birth

Abstract: Despite major advances in neonatal care, the burden of preterm birth remains high. This is not unexpected since strategies to identify and treat risk factors in early pregnancy have not been very effective in reducing the preterm birth rate. Initial studies suggested a potential benefit for 17- alpha-hydroxyprogesterone caproate (17-OHPC) in decreasing the risk of recurrent preterm birth women with a singleton gestation. However, the use of 17-OHPC has not conferred benefit for other categories of women at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Initial studies suggested a potential benefit for 17-alpha-hydroxyprogesterone caproate (17-OHPC) in decreasing the risk of recurrent preterm birth women with a singleton gestation. However, the use of 17-OHPC has not conferred benefit for other categories of women at high risk for preterm delivery (twins, triplets, and short cervical length) [26]. In this study, patient satisfaction with its use was significantly better than oral progesterone despite injection site problems in 20% of cases.…”
Section: Discussionmentioning
confidence: 56%
“…Initial studies suggested a potential benefit for 17-alpha-hydroxyprogesterone caproate (17-OHPC) in decreasing the risk of recurrent preterm birth women with a singleton gestation. However, the use of 17-OHPC has not conferred benefit for other categories of women at high risk for preterm delivery (twins, triplets, and short cervical length) [26]. In this study, patient satisfaction with its use was significantly better than oral progesterone despite injection site problems in 20% of cases.…”
Section: Discussionmentioning
confidence: 56%
“…Sterile compounding involves a great deal of risk compared to product manufacturing by a pharmaceutical company. In spite of the enforcement of USP <797> by the FDA, there are plenty of cases reported where poor compounding practice or compounding error resulted in severe consequences or deaths [7,35]. Very recently AMAG pharmaceuticals has introduced a single-dose generic version of preservative-free Makena ® to circumvent such issues.…”
Section: Discussionmentioning
confidence: 99%